KARAKTERISTIK FISIK, KIMIA, DAN SENSORIS FRUIT LEATHER PISANG AMBON (Musa paradisiaca S.) DENGAN PENAMBAHAN GULA DAN KARAGENAN - Ages Dwiga Marzelly; Triana Lindriati; Sih Yuwanti (JURNAL AGROTEKNOLOGI, 2017)
Fruit leather is a fruit product that has been destroyed and then dried using an oven, so as to form a thin sheet that can be rolled. Fruit leather is generally a thin sheet with a thickness of 2-3 mm, 10-20% water content, plastis texture, was a consistency and a specific taste according to the type of fruit used. Ambon banana has a low pectin content that requires a gel-forming agent to produce the desired texture. One of the commonly used gelling materials is carrageenan. Carrageenan is one of the seaweed derived hydrocolloids that have the ability to form gel and can improved the texture of the product. Carrageenan in gel form must have a dehydrating compound. The common dehydrating agent is sugar. Sugar is a material that can attract water molecules that bind to carrageenan molecules, so that sugars can make a solid gel. The purpose of the study to determine the effect of additional sugar and carrageenan concentration on physical, chemical, and sensory characteristics of fruit leather of Ambon banana and to determine the amount of additional of sugar and carrageenan concentration according to sensory data to produce fruit leather with good sensory characteristics. This study used Completely Randomized Design (RAL) consisting of two factors and three replications. The first factor is the percentage of sugar consisting of 5%, 10%, and 15%. The second factor is the percentage of carrageenan consisting of 0.3%, 0.6%, and 0.9%. Tests carried out include physical characteristics (lighness, texture, tensile strength, and elongation), chemical characteristics (moisture content and ash content), as well as sensory characteristics (color, taste, aroma, texture and overall). The data obtained is processed using a fingerprint analysis analysis of variance using Minitab program V.1.7. If there is a significant difference or influence, then a tukey test on test level α ≤ 5% is used. The result of this research showed that the production of fruit leather of banana Ambon with the concentration of sugar and carrageenan added has a significantly characteristic sensory taste and texture, while no significant effect on the sensory characteristics of color, aroma, overall, physical characteristics (lightness, texture, elongation and tensile strength) and chemical characteristics (ash and water content). Determination of the best treatment in this study was found in A2B1 treatment using 10% sugar concentration and 0.3% carrageenan with a very liking assessment as follows 3% color; aroma 13%; 17% texture; 13% taste; and overall 13% with a total value of 59%. Keywords: caragenan, fruit leather, sugar